A test design for measuring power uptake of bicycle bottom bracket bearing assemblies - Buder, J.; Schwanitz, S.; Odendwald, S.; Huang, J. (Journal of Science and Cycling, 2024)
The scope of this study was to develop a test design to quantify the power uptake of bicycle bottom bracket bearings. For this, a caloric, contactless measurement laboratory design was set up with the potential extend to field application. The goal was to determine differences in resistance of 30 given bearing assemblies. The assemblies have been systematically modified in order to impact the power uptake during cycling relevant revolutions. Also 3 standard bearing assemblies have been tested for reference. In this test design, each sample was mounted into a vice, comprising a bottom bracket shell, a spindle, corresponding with the bearing dimension and two disks mounted on each side of the spindle`s endings. For each run of the tests, the two discs and the spindle were set into rotation, exceeding 200 rpm and then let itself slowdown until a complete stop. During each of the runs, the angular velocity of the rotating disks was measured. The inertia of the rotating parts at a certain angular velocity represents the rotational energy in the system, hence its decrease over time the power uptake by the bearings. The tests revealed statistically significant differences in resistance amongst the 33 samples of up to 769%. A re-test was done in order to validate the designs reliability which revealed a high level of repeatability and reproducibility.